Functional characterization of elderly people in the rural community of "Lagunillas". January-March 2004. - Marly Delgado Navarro; Luz María Díaz Hernádez; Fidelina Bravo Vargas (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2005)
Fundament: Aging in human beings is the result of a very complex interaction of biological, psychological and social factors. In this stage, not only health problems are affected but also also another group of factors which are called social risk of aging. Objetive : To assess the fctional capacity of elders in a rural community Methods: Correctional transversal descriptive study carried out in theconsulting room number 13 that belong to the policlinic area VIII from Cienfuegos. The study gathered a total of 45 old patients who were selected at random, constituting 47% of the universe which is formed by 96 elders. The variables under study were : age, sex, marital status, occupational situation, and scholarship. The geriatric scale of functional assessment was applied to each of them. Results: Most of them (75,5%) has a satisfactory global functional assessment,. Their mood is fine mainly for those who have a good familial care, the married elders and those who have no difficulties with their basic necessities. There are no signs of an important lack of mobility, audition , sight, sleep and continence in the sample under study. The geriatric population was found to be functionally active.